Pasados presentes : tradiciones historiográficas en la musicología europea (1870-1930) - Bombi, Andrea (Col·lecció Oberta ;, 2016)
The seven essays in this book delve into the similiarities and differences of the musicological traditions of Germany, Spain, France, and Italy at the end of the 19th and beginning of the twentieth centuries.